ANALISIS PENGGUNAAN SELF CHECK-IN DALAM MENUNJANG KELANCARAN CHECK-IN DI BANDAR UDARA AHMAD YANI SEMARANG - Naufal Tegar Afgani (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Ahmad Yani International Airport in Semarang, Central Java, Indonesia, experienced rapid growth in flight frequency and passenger numbers. To improve efficiency, self check-in facilities were introduced as a practical alternative to the manual check-in process. This study aims to analyze the use of self check-in in expediting the check-in process and identify obstacles faced by passengers and their solutions. The method used is descriptive qualitative, including observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that although the self check-in facility has been well implemented and supported by officers, passengers still face several obstacles. The main obstacles include the limited number of airlines that can be accessed through self check-in machines and passengers' lack of understanding of this technology. Problem solving can be done by improving passenger understanding and expanding the range of airlines available on self check-in machines